2019
DOI: 10.33005/jasf.v2i2.49
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effect of Liquidity, Leverage, Sales Growth, and Good Corporate Governance on Financial Distress

Abstract: Large companies may experience financial distress because of their inability to compete. Therefore, investors should be more vigilant in investing their funds. Some ways that can be done is through cash flow analysis, analysis of corporate strategy, and analysis of financial statements. This study aims to determine the effect of liquidity, leverage, sales growth, and good corporate governance on financial distress. The study used 55 samples of telecommunication and non-construction companies listed in Indonesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
19

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 6 publications
0
12
0
19
Order By: Relevance
“…Studies that used GCG as variable are Dianova and Nahumury (2019), Hilaliya and Margaretha (2017), Juniarti (2013), Cahyani and Diantini (2016), and others. Next, the studies that used liquidity, profitability, leverage, and activity as variables are Nurfajrina et al (2016), (Heniwati and Essen (2020), Pujiastuti and Yuharningsih (2014), Oktarina (2017), Utami and Kartika (2019), Sumani (2019), Antikasari and Djuminah (2017), and (Mafiroh and Triyono (2018).…”
Section: Table 4 Articles Distributions Based On Internal Factor Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies that used GCG as variable are Dianova and Nahumury (2019), Hilaliya and Margaretha (2017), Juniarti (2013), Cahyani and Diantini (2016), and others. Next, the studies that used liquidity, profitability, leverage, and activity as variables are Nurfajrina et al (2016), (Heniwati and Essen (2020), Pujiastuti and Yuharningsih (2014), Oktarina (2017), Utami and Kartika (2019), Sumani (2019), Antikasari and Djuminah (2017), and (Mafiroh and Triyono (2018).…”
Section: Table 4 Articles Distributions Based On Internal Factor Variablesmentioning
confidence: 99%
“…Previous studies gave empirical evidence of financial distress using internal indicators, such as financial conditions and corporate governance, which gave different results. Dianova and Nahumury (2019) found that liquidity ratio, leverage, sales growth, and corporate governance do not affect financial distress. Fahlevi and Mukhibad (2018) found that liquidity, profitability, and leverage do not affect financial distress.…”
Section: Introductionmentioning
confidence: 97%
“…Financial distress is terrible news for company financial reports (Muliantari & Latrini, 2017). Financial distress can be seen from the ratio between the company's long terms debt and total assets owned (Dianova & Nahumury, 2019). For companies, they will avoid publication if the company is experiencing difficult financial conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Hal ini dikarenakan tingginya tingkat Sales Growth tidak selalu memiliki beban yang sedikit sedikit, sehingga laba bersih yang dihasilkan hanya sedikit atau tidak mencapai target bahkan bisa negative, hal tersebut dapat berdampak terhadap kondisi keuangan perusahaan yang dapat memungkinkan terjadinya Financial Distress di masa mendatang. Penelitian ini sejalan dengan penelitian ( Rahmy, 2015;Prasetya, 2021;Dianova, 2019;dan Giarto ; yang menyatakan bahwa sales growth tidak berpengaruh terhadap Financial Distress. Hasil penelitian Amanda (2019) menyatakan hasil yang berbeda yakni sales growth berpengaruh terhadap Financial Distress.…”
Section: Pengaruh Sales Growth Terhadap Financial Distressunclassified